2018
DOI: 10.3390/ijms19113411
|View full text |Cite
|
Sign up to set email alerts
|

A Molecular Biophysical Approach to Diclofenac Topical Gastrointestinal Damage

Abstract: Diclofenac (DCF), the most widely consumed non-steroidal anti-inflammatory drug (NSAID) worldwide, is associated with adverse typical effects, including gastrointestinal (GI) complications. The present study aims to better understand the topical toxicity induced by DCF using membrane models that mimic the physiological, biophysical, and chemical environments of GI mucosa segments. For this purpose, phospholipidic model systems that mimic the GI protective lining and lipid models of the inner mitochondrial memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 82 publications
(211 reference statements)
6
43
0
Order By: Relevance
“…Experimental data from this study suggested that neutral diclofenac has a deeper preferential location in the DMPC bilayer, putatively establishing H-bonds with the DMPC's phosphate group and disrupting the lipid-lipid interactions in the inner region of the acyl chains. On the other hand, anionic diclofenac seems to have a shallower location, probably because of electrostatic adsorption in the DMPC's choline group, as previously reported (Ferreira et al, 2005;Manrique-Moreno et al, 2009;Fernandes et al, 2018). This hypothesis is in agreement with molecular dynamics simulations that indicate that neutral NSAIDs are located closer to the bilayer center than anionic NSAIDs (Boggara and Krishnamoorti, 2010;Markiewicz and Pasenkiewicz-Gierula, 2011).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Experimental data from this study suggested that neutral diclofenac has a deeper preferential location in the DMPC bilayer, putatively establishing H-bonds with the DMPC's phosphate group and disrupting the lipid-lipid interactions in the inner region of the acyl chains. On the other hand, anionic diclofenac seems to have a shallower location, probably because of electrostatic adsorption in the DMPC's choline group, as previously reported (Ferreira et al, 2005;Manrique-Moreno et al, 2009;Fernandes et al, 2018). This hypothesis is in agreement with molecular dynamics simulations that indicate that neutral NSAIDs are located closer to the bilayer center than anionic NSAIDs (Boggara and Krishnamoorti, 2010;Markiewicz and Pasenkiewicz-Gierula, 2011).…”
Section: Discussionsupporting
confidence: 90%
“…It is noteworthy that the neutral diclofenac-induced effects on the phosphatidylcholine bilayers were often more pronounced and/or distinct than that caused by anionic diclofenac. In fact, the diclofenac-induced decrease of the temperature and cooperativity of the main phase transition of DMPC bilayers at pH 7.4 and 5.0 was previously reported elsewhere (Manrique-Moreno et al, 2009;Fernandes et al, 2018). However, more pronounced alterations were observed with neutral diclofenac in this study, considering equivalent membrane concentrations.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Static exposures were taken below and above the main transition temperature as controlled by a thermostated water bath (stability ± 0.1 °C; Unistat CC, Huber, Offenburg, Germany) in order to obtain the diffraction patterns typical of DPPC lipid phases (L β′ and L α ) and evaluate the effect of drugs in such phases. Data analysis was made as described elsewhere [30].…”
Section: Methodsmentioning
confidence: 99%